The Role of Transformational Leadership, Organizational Learning and Structure on Innovation Capacity: Evidence from Indonesia Private Schools - Hatoli Waruwu; Masduki Asbari; Agus Purwanto; Yunianto Agung Nugroho; Muhamad Agung Ali Fikri; Ahmad Fauji; Abdul Wahid Imam Shobihi; Paolinus Hulu; Rachma Nadhila Sudiyono; Eva Agistiawati; Wulan Rahma Dewi (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This study aims to measure the effect of transformational leadership, organizational learning and organizational structure on the teacher innovation capacity. Data collection was carried out by simple random sampling via electronic on the population of private school teachers in Indonesia. The returned and valid questionnaire results were 645 respondents in the sample. Data processing using SEM method with SmartPLS 3.0 software. The results of this study are transformational leadership, organizational learning and organizational structure have a positive and significant effect on innovation capacity. Transformational leadership has a positive and significant effect on organizational learning and organizational structure. This novel research is proposing a model of building the teacher innovation capacity through transformational leadership in the perspective of learning organizations and organizational structure. This research can pave the way to improve the readiness of the teachers in Indonesia, especially the teachers of private schools to face the industrial revolution 4.0.